Pereira, Maria Isabel; Santos, Silvio Aparecido dos, “Modelo de gestão: uma análise conceitual". São Paulo: Pioneira Thomson Learning, 2001. 71 p. - Soares da Costa, Wellington (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
Sin resumen